First report of Chrysodeixis includens nucleopolyhedrovirus (ChinNPV) infecting Chrysodeixis includens (Lepidoptera: Noctuidae) in Argentina - Arneodo Larochette, Joel Demian; Dami, Luciana Cecilia; Jakubowicz, Violeta; Alzogaray, Raúl Adolfo; Taibo, Catalina Beatriz (2018)
Typical baculovirus infection symptoms were observed in Chrysodeixis includens Walker (Lepidoptera: Noctuidae) larvae from a laboratory rearing in Tucumán, Argentina. Scanning electron microscopy revealed the occurrence of polyhedral occlusion bodies displaying a heterogeneous morphology. Amplification, sequencing, and phylogenetic analysis of conserved polyhedrin, lef-8 and lef-9 genes identified the pathogen, for the first time in Argentina, as a variant of Chrysodeixis includens nucleopolyhedrovirus (ChinNPV). The biocontrol potential of this new isolate is worthy of future research.